If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7 = 2x + -4 Reorder the terms: -7 + 4x = 2x + -4 Reorder the terms: -7 + 4x = -4 + 2x Solving -7 + 4x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + 4x + -2x = -4 + 2x + -2x Combine like terms: 4x + -2x = 2x -7 + 2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + 2x = -4 + 0 -7 + 2x = -4 Add '7' to each side of the equation. -7 + 7 + 2x = -4 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = -4 + 7 2x = -4 + 7 Combine like terms: -4 + 7 = 3 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5
| x+iy=4-2i | | y^2+19y+84= | | 7(1-2x)=-6x-33 | | 62=8n-2 | | 2(x+1)=x-9 | | 8x-7w+4x+8y+3y+5w= | | -x-17=-4x+1 | | c+18=50 | | -6=2z+14 | | 4x-1+2x=5x+4x | | 1.16x=5.80 | | -y+7=2y+7 | | 35-3v=2v+5 | | 8x+2(-5-3x)=8-7x | | 0=7w-34 | | 6y-42=5y+20 | | b-14=28 | | 6n^2+18n=0 | | 3n+10=91 | | 3(x+3)=14 | | (12m-10)(10m+10)= | | 10x-9y+13=0 | | 4m+2=30 | | 5(8-6x)=-7x+2(-8x-8) | | -0.1x-5x=-18.87 | | 12m-10= | | -x+1=-7x+1 | | a+22=52 | | 5x+26+3x+60=180 | | 4x+2y+0.25z=100 | | 0+y=0 | | 5x+26=3x+60 |